Re-examining money market and economic growth nexus in Nigeria: A SVAR model approach - Ganiyat Adejoke Adesina-Uthman; Adenuga Adeniyi Olatunde; Itodo Idoko Ahmed (West African Journal of Monetary and Economic Integration, 2020)
Money market and economic growth nexus has been debated in the literature. This paper therefore re-examines money market impact on economic growth in Nigeria using quarterly data from 2000Q1 to 2018Q4. It utilised the structural vector autoregressive (SVAR) model framework to generate the impulse responses, and variance decomposition of economic growth in Nigeria, resulting from shocks to treasury bills, prime lending rate, maximum lending rate, and money supply growth rate. The findings from the structural VAR model suggest that, while shocks to money supply growth, prime- and maximum lending rates have negative instantaneous impacts on economic growth, shocks to treasury bills rate has a positive instantaneous impact on output growth. This evidence will be useful to the monetary authorities to allow policy decisions to run its course before pronouncing a fresh one on the same issue. The development will also help to avoid policy inconsistency
Keywords: A1; D53; E12; 330; Money Market; Economic Growth; Nigeria